Turbulence regulation of Microcystis surface scum formation and dispersion during a cyanobacteria bloom event. Issue 1 (2nd January 2020) - Hozumi, Aya; Ostrovsky, Ilia; Sukenik, Assaf; Gildor, Hezi
ABSTRACT: Microcystis blooms are a global problem adversely affecting the quality of freshwater in lakes and reservoirs. Surface scum (0–1 m) forms as a result of vertical migration by buoyant Microcystis colonies. Accurate forecasting of bloom and scum development is essential for establishing a reliable alert system and requires understanding the role that physicobiological factors play in the vertical distribution of Microcystis in natural ecosystems. We researched the role of limnological processes on the vertical distribution of Microcystis colonies in Lake Kinneret (max depth = 38 m) during a winter–spring bloom. We used measurements from a Laser In situ Scattering and Transmissometry profiler and a plankton image analyser, FlowCAM. Various hydrometeorological conditions were captured during 6 outings from 9 February to 21 March 2017. Thermal stratification and turbulence levels influenced the vertical distribution of Microcystis colonies and scum formation. During periods of weak turbulence (e.g., vertical turbulent eddy diffusivity [ Kz ] <1 cm 2 s −1 ), the volume concentration of Microcystis colonies near the surface abruptly increased. High turbulence levels (e.g., windy conditions) dispersed colonies concentrated near the surface. Simulations of the vertical distribution of Microcystis colonies under different turbulence levels showed that the thickness of the surface scum layer increased and colony concentration of scum decreased as turbulence level increased. We demonstrated that Kz >3 cm 2 s −1, driven by the wind and surface heating/cooling, dispersed the surface layer of concentrated Microcystis colonies. Our results revealed an underlying interdependency between environmental factors and Microcystis colony distribution that can be utilized to accurately forecast scum formation.